THE EFFECT AND SAFETY OF BERBERINE ON POLYCYSTIC OVARY SYNDROME : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The isoquinoline derivative alkaloid known as berberine (BBB) can be found in the Chinese medicinal herbs Coptidis Rhizoma (Huanglian), Cortex Phellodendri (Huangbai), and Hydrastis Canadensis. These three plants are also the sources of berberine. Since the time when Iranians' ancestors first settled the region, they have made advantage of the unique features that B. vulgaris contains and have done so ever since. For instance, the dried fruits of this plant have been used as an ingredient in food. Additionally, the root, bark, leaf, and fruit of this plant have all been widely exploited as a folk medicine for the treatment of a wide variety of ailments. According to study that was carried out in both vitro and in vivo, it was recently discovered that berberine possesses the potential to reduce glucose levels in people who are afflicted with diabetes and obesity. The precise method by which berberine is able to treat diabetes is not fully understood at this time. In the research that Ko and his colleagues conducted, they found that berberine enhanced the insulin/insulin-like growth factor-1 signaling cascade in Min6 cells, which led to an increase in the amount of insulin that was produced in response to glucose stimulation. Pregnancy rates improved with BBR medication only among infertile women who had taken BBR prior to undergoing IVF, as shown by other studies; this was not the case for all infertile women. Other studies indicated that this was not the case. PCOS women who were treated with BBR saw improvements in their hormonal profile, menstrual cycle, and WHR. Only in infertile women who utilized BBR prior to undergoing IVF did BBB show successful in improving pregnancy rates. The BBR was secure. The findings should be treated with some degree of caution due to the limited amount of study and the size of the sample.